POTENSI PENINGKATAN EUROSKEPTISISME DI NEGARA INTI UNI EROPA - Pradana, Hafid Adim; Ramadhoan, Ruli Inayah (JPP (Jurnal Politik Profetik), 2019)
The recent eradication of immigration and financial crises faced by the European Union has revived doubts from EU member states that they will need to survive in the European Union. This became known as Euroskepticism. The exit of the UK from the European Union after the Brexit referendum in 2016 further strengthened the notion of a strengthening euroskepticism in European Union countries. Departing from this, this study seeks to find out how significant the development of euroskepticism in European Union countries, which includes France, the Netherlands, Germany, Italy, Belgium and Luxembourg, through comparison of the results of inter-party contestation in the last three elections. The six countries were chosen because they are the core countries that started the formation of European integration. The indicator used to measure the development of euroskepticism is by looking at the results of the right-wing or nationalist party results in each general election. Using comparative methods and quantitative data analysis techniques, this study produced findings that there was a significant increase in euroskepticism in France, the Netherlands, and Italy, and the potential to hold a referendum as the British had done.